1084 UNUSUAL LABORATORY FINDINGS IN ECHOVIRUS-11 MENINGITIS - Thompson, C Hurry (Pediatr Res, 1981)
Echovirus 11(E-11) was isolated from the cerebrospinal fluid (CSF) of 22 children in a 1980 summer outbreak of meningitis. Seventeen(77%) were <6 mos old(range 2 wk-9 yr). 54% had CSF cell counts >300/mm(3) and 14% had >500/mm(3)(range 0-2250). 59% had ≥50% polymorphonuclears(P) and 24% had >90% P. None had CSF glucose <40mg/dl; 41% had CSF protein ≥45mg/dl and 6% had >75mg/dl. Three patients(pts) had entirely normal CSF. In 86% peripheral WBC was 5000-15000/mm(3); only 3 had >75% P but 20% had absolute band count >500/mm(3) Four pts(<3 mos old) had repeat CSF exams. All had >50 cells/mm(3) and the two youngest(age 2 wk) still had >50% P after 1 and 3 days. CSF findings were compared with data from pts with bacterial meningitis(B). Cell count >500/mm(3), glucose ≤45mg/dl, and protein >75mg/dl were statistically associated with B. However, 14% of E-11 pts had at least one of these findings and 20% of B pts had none of these findings. CSF P >75% was as frequent in E-11 pts as in B pts. Peripheral WBC <5000 or >15000/mm(3) and absolute band count >500/mm(3) were statistically associated with B but 38% of E-ll pts had one of these abnormalities. Certain CSF findings in our pts have not been reported for E-11 and are uncharacteristic of viral meningitis: 1) leukocyte response more characteristic of bacterial meningitis: CSF P >90%, persistence of CSF P beyond 24 hrs, peripheral band count >500, and 2) entirely normal CSF.